DECISION SUPPORT WORTHINESS INPATIENT ROOM AT REGIONAL PUBLIC HOSPITAL PRINGSEWU USING SIMPLE ADDITIVE WEIGHTING METHOD - Sri Rahayu Ningsih; Fauzi Fauzi; Fiqih Satria (STMIK Pringsewu Lampung, 2017)
Health is one requirement for humans. Health care is a process to provide facilities for patients treated in hospitals Pringsewu. As well as it is a basic requirement for controlling and maintaining quality of service. One that affects the quality of health care is the worthiness of inpatient room at the grade 3 in hospital Pringsewu. This study is focus on emphasizes the purpose of the system worthiness inpatient is to determine the worthiness of inpatient grade 3 in hospital Pringsewu, furthermore in this study can give a solution to improve the quality of inpatient grade 3 Hospital by delivering systems decision support to determine the worthiness of inpatient grade 3 that can be used to support the evaluation of service in hospital Pringsewu. The research conducted in hospitals Pringsewu by using Simple Additive Weighting method (SAW). The goal of this research was to determine the worthy or not the inpatient in hospitals Pringsewu. The determination of worthiness decision system's inpatient with a view of seven assessment criteria such as service duty, sleeping facilities, showers, support facilities, oxygen, waiting room services and technical services. Based on the calculation the results obtained SAW, among others: the room is very worthy is C room value of 0.66, adequate is A room value of 0:59, room E value of 0:58, room B value of 0:57, and the room was not worth D value of 0:31